The interplay between theory and practice: Mathematics pre-service teachers’ learning experiences at a teaching school - Spangenberg, Erica (The IIE, 2017)
South Africa has insufficient pedagogies in teacher education that integrate pre-service teachers’ experiences of theory at universities with their practical experiences in teaching schools (TSs). This paper examines mathematics pre-service teachers’ learning experiences at a TS converging on the interplay between theory and practice. A three-level model proposed by Korthagen (2010), consisting of a gestalt-, schema- and theory-level, which built on the situative perspective, was used to frame the study. A case study using a qualitative research design was adopted with two data collection methods, namely, interviews and reflection reports. A sample of five mathematics pre-service teachers (PTs) enrolled for a Postgraduate Certificate in Education (PGCE) qualification, was purposefully selected. The results indicate most PTs could act and reflect on gestalt-driven experiences, however, an appropriate theory-level was not reached. At the gestalt-level most PTs viewed mathematics as abstract, theoretical and complex, and considered the teaching and learning of mathematics to be skill-driven. At the schema-level three PTs applied mathematics to real-life activities and reflected and acted intentionally in the teaching-and-learning process. At the theory-level all PTs coherently arranged some of their knowledge and considered the impact of their teaching on learners. The study contributes by providing a context to investigate the interchange between theory and practice.
Keywords: Mathematics; Pre-service teachers; Learning theory